2013
DOI: 10.1080/00102202.2012.716108
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on a Layer of HMX Explosive Crystals in Response to Drop-Weight Impact

Abstract: Drop-weight experiments are performed on a thin layer of cyclotetramethylene tetranitramine (HMX) explosive crystals. The drop-weight impact machine is equipped with high-speed photographic systems. Experimental results show the effects of drop heights, mass of particles, and distributed density on compaction, deformation, transparency, reaction violence, and burning propagation. The aim is to establish a link between mechanical and thermal responses for a single layer of granular explosives. Minimum input ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The ignition and growth reactive flow model has been widely used for its good performance in characterizing the shock initiation process of energetic materials. In this model, the Jones-Wilkins-Lee (JWL) equations of state of the unreacted explosive and the reaction products are both in temperature dependent form (1) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 (2) in which p is pressure, V is relative volume, w is the Gruneisen coefficient, C V is average heat capacity, T is temperature, and A, B, R 1 , R 2 are constants. The subscript e and g denote the unreacted explosive and the reaction products, respectively.…”
Section: Equation Of State Parameters Of Reactants and Detonation Promentioning
confidence: 99%
See 1 more Smart Citation
“…The ignition and growth reactive flow model has been widely used for its good performance in characterizing the shock initiation process of energetic materials. In this model, the Jones-Wilkins-Lee (JWL) equations of state of the unreacted explosive and the reaction products are both in temperature dependent form (1) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 (2) in which p is pressure, V is relative volume, w is the Gruneisen coefficient, C V is average heat capacity, T is temperature, and A, B, R 1 , R 2 are constants. The subscript e and g denote the unreacted explosive and the reaction products, respectively.…”
Section: Equation Of State Parameters Of Reactants and Detonation Promentioning
confidence: 99%
“…It is commonly accepted that the formation of hot spots results in the initiation. Several of mechanisms such as localized adiabatic shear, void collapse, interface friction and viscous heating in the energetic material lead to the formation of the hot spots [1,2]. Theoretical models are developed to describe the shock initiation and energy release process quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a 175 mm American artillery loaded with Composition B (COM B) explosive charge, the bore burst rate is reportedly as high as 0.04% [2], resulting in serious weapon destruction and casualties. The accidental ignition of explosive charges in the launch environment is one of the primary reasons for bore bursts, the mechanism of which has been the focus of considerable research on the launch safety of explosive charges [3,4]. Many scholars [5][6][7][8][9][10] have examined the stress, action time, and hot-spot generation of an explosive charge in the launch environment, finding that factors influencing accidental ignition are the particle size, pores, bottom gaps, cracks, and other defects associated with the explosive charge [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Drop weight impact testing shows that HMX microcrystals of nanoscale size are much less sensitive than HMX bulk crystals [5]. Wu and Huang [6] have used high-speed photography to record the impact response behavior of the monolayer HMX particles under drop weight and analyzed its ignition mechanism. An et al [7] found that the mechanical sensitivity of HMX reduces obviously if it covered with HTPB.…”
Section: Introductionmentioning
confidence: 99%